Think Tanks in Nepal: Emergence and Growth - Shah, Birendra Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
Think tank is bridging gap among academic and policy making communities, states and civil society to serve in the public interest as independent voices that translate applied and basic research into a language, form that is understandable, reliable, and accessible for policy makers and the public. Hence, Nepal is officially far from it. Although, practices in Nepal is very limited as well as narrow ideas, thinking, and approaches to sake prosperities of divergent Nepali societies and cultures. Government investment is very poor in these works. However, newly opened universities, private institutions and NGOs are work like as hybrid, are engaged in educational research activities. Over the last 10-15 years, governments, and civil society have come to rely on it, and this trend will continue to input better future of Nepal. DOI: http://dx.doi.org/10.3126/av.v4i0.12351 Academic Voices Vol.4 2014: 17-20